A composite material for lithium ion battery positive electrode and its preparation method and application

The titanium silicon sol prepared by La/Ce doping undergoes self-propagation combustion reaction with Mn3O4, and through polydopamine coating modification treatment, a composite material for positive electrode of lithium ion batteries was prepared, solving the problem of capacity attenuation of lithium manganate positive electrode material and poor production process stability, achieving better cycle performance and high temperature stability.

CN119370892BActive Publication Date: 2025-03-28ZHUZHOU SHENGHUA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411942807.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing lithium manganate positive electrode materials have a fast capacity decay during the charge and discharge cycle, especially at high temperatures, and have poor production process stability, resulting in high reactivity between the material and the electrolyte.

Method used

The titanium silica sol prepared by La/Ce doping was carried out in a self-propagation combustion reaction with Mn3O4, and then it was coated with polydopamine and mixed with lithium carbonate and potassium oxide for three-stage calcination to prepare a composite material for the positive electrode of lithium-ion batteries.

Benefits of technology

The circulation performance of lithium manganate is improved, the internal resistance of the electrode is reduced, the specific capacity of large-rate discharge is improved, the speed performance and high temperature cycle stability are better, and the capacity retention rate for multiple cycles is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention proposes a composite material for positive electrode of lithium ion battery and its preparation method and application, which belongs to the technical field of positive electrode materials. La / Ce doped silicon titanium sol is prepared, Mn3O4 is added, heated to carry out self-propagating combustion reaction, the surface is modified by coating with polydopamine, mixed with lithium carbonate and potassium oxide and ball milled, calcined in three stages, cooled to room temperature, and the composite material for positive electrode of lithium ion battery is obtained. The composite material for positive electrode of lithium ion battery prepared by the present invention improves the cycle performance of lithium manganese oxide, reduces the internal resistance of the electrode, improves the high-rate discharge specific capacity, has better rate performance and high-temperature cycle stability, has a high capacity retention rate for multiple cycles, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a composite material for positive electrode of a lithium ion battery and a preparation method and application thereof. Background Art

[0002] In recent years, the application of lithium-ion batteries in electric vehicles (high power density devices) and energy storage (high energy density devices) has attracted widespread attention. As an important component of lithium-ion batteries, cathode materials play a decisive role in the battery's operating voltage, cycle life, capacity, safety and other performance. Therefore, research and development of high-capacity, long-life, and high-safety cathode materials is one of the key points in lithium-ion battery research.

[0003] At present, the cathode material of commercial lithium-ion batteries is traditional lithium cobalt oxide, which has a low actual capacity (about 140 mAhg -1 ), the transition metal cobalt is expensive and highly toxic, so its application in the field of electric vehicles is limited. However, green and non-toxic spinel lithium manganese oxide has attracted widespread attention due to its high rate performance, relatively low cost, and environmental friendliness.

[0004] Although lithium manganese oxide has many advantages, its fatal flaw is that its capacity decays rapidly during the charge and discharge cycle, and the decay is more obvious at high temperatures. The reasons are: (1) The purity of the synthesized material is not high and the morphology is irregular, which leads to a high reaction activity between the material and the electrolyte, resulting in accelerated manganese dissolution; (2) The material has a Jahn-Teller effect. As the number of charge and discharge times increases, the material is distorted and the capacity decreases rapidly.

[0005] Then the above-mentioned shortcomings of lithium manganese oxide can be improved in the synthesis process, so that the material performance is greatly improved. The commonly used method in the production of lithium manganese oxide is the solid phase method, that is, dry mixing manganese sources such as manganese dioxide and manganese carbonate with lithium carbonate and lithium hydroxide. After the two components are evenly mixed, they are calcined at high temperature to finally synthesize the finished product. However, this method cannot evenly mix the lithium salt into the interior of the manganese source, and the synthesized lithium manganese oxide particles have obvious edges and corners, which results in poor stability of the synthesis process, and increases the activity of the reaction between lithium manganese oxide and the electrolyte, resulting in poor circulation. Summary of the invention

[0006] The purpose of the present invention is to provide a composite material for lithium ion battery positive electrode and its preparation method and application, improve the cycle performance of lithium manganese oxide, reduce the internal resistance of the electrode, improve the high-rate discharge specific capacity, have better rate performance and high-temperature cycle stability, high capacity retention rate for multiple cycles, and have broad application prospects.

[0007] The technical solution of the present invention is achieved in this way:

[0008] The invention provides a method for preparing a composite material for a positive electrode of a lithium ion battery. The method comprises the following steps: preparing La / Ce doped silicon titanium sol, adding Mn3O4, heating to carry out a self-propagating combustion reaction, modifying the surface by coating with polydopamine, mixing with lithium carbonate and potassium oxide, ball milling, calcining in three stages, and cooling to room temperature to obtain the composite material for a positive electrode of a lithium ion battery.

[0009] As a further improvement of the present invention, the following steps are included:

[0010] S1. Preparation of La / Ce-doped silica-titanium sol: lanthanum chloride and cerium chloride were dissolved in water to obtain solution A, alkyl orthosilicate and tetrabutyl titanate were dissolved in ethanol to obtain solution B, solution A and solution B were mixed uniformly, hydrochloric acid was added dropwise to form a sol, and La / Ce-doped silica-titanium sol was obtained;

[0011] S2. Preparation of La / Ce-doped Si / Ti oxide-coated Mn3O4 powder: Mn3O4 was added to La / Ce-doped silicon-titanium sol, stirred and mixed evenly, and heated for self-propagating combustion reaction to obtain fluffy La / Ce-doped Si / Ti oxide-coated Mn3O4 powder;

[0012] S3. Polydopamine modification: La / Ce-doped Si / Ti oxide-coated Mn3O4 powder was added to water, dopamine hydrochloride and a catalyst were added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain a modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder;

[0013] S4. Calcination: The modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder, lithium carbonate and potassium oxide are mixed and ball-milled, calcined at a first temperature for a first period of time, heated to a second temperature, calcined for a second period of time, heated to a third temperature, calcined for a third period of time, and cooled to room temperature to obtain a composite material for a positive electrode of a lithium-ion battery.

[0014] As a further improvement of the present invention, the mass ratio of lanthanum chloride, cerium chloride, alkyl orthosilicate, tetrabutyl titanate and hydrochloric acid in step S1 is 1-2:2-3:15-20:8-10:7-10, and the concentration of hydrochloric acid is 1-2 mol / L.

[0015] As a further improvement of the present invention, the heating in step S2 is to a temperature of 180-200°C.

[0016] As a further improvement of the present invention, the mass ratio of Mn3O4, La / Ce doped silica-titanium sol, dopamine hydrochloride, catalyst, lithium carbonate and potassium oxide is 10:20-30:4-6:0.5-1:2-2.4:0.01-0.02.

[0017] As a further improvement of the present invention, the temperature of the heating and stirring reaction in step S3 is 40-50° C., the time is 3-5 hours, and the catalyst is a Tris-HCl solution with a pH of 8.5-9.5.

[0018] As a further improvement of the present invention, the ball milling time in step S4 is 1-3h, the first temperature is 300-400°C, the time is 1-5h, the second temperature is 500-600°C, the time is 1-5h, and the third temperature is 700-900°C, the time is 2-15h.

[0019] As a further improvement of the present invention, the present invention specifically comprises the following steps:

[0020] S1. Preparation of La / Ce-doped silicon-titanium sol: 1-2 parts by weight of lanthanum chloride and 2-3 parts by weight of cerium chloride are dissolved in water to obtain solution A, 15-20 parts by weight of alkyl orthosilicate and 8-10 parts by weight of tetrabutyl titanate are dissolved in ethanol to obtain solution B, solution A and solution B are uniformly mixed, 7-10 parts by weight of 1-2 mol / L hydrochloric acid is added dropwise to form a sol, and La / Ce-doped silicon-titanium sol is obtained;

[0021] S2. Preparation of La / Ce doped Si / Ti oxide coated Mn3O4 powder: 14-15 parts by weight of Mn3O4 is added to 20-30 parts by weight of La / Ce doped silicon-titanium sol, stirred and mixed for 30 minutes, heated to 180-200°C, and subjected to self-propagating combustion reaction to obtain fluffy La / Ce doped Si / Ti oxide coated Mn3O4 powder;

[0022] S3. Polydopamine modification: The La / Ce-doped Si / Ti oxide-coated Mn3O4 powder obtained in step S2 is added to water, 4-6 parts by weight of dopamine hydrochloride and 0.5-1 parts by weight of a catalyst are added, heated to 40-50°C, stirred for 3-5h, centrifuged, washed, and dried to obtain a modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder;

[0023] The catalyst is a Tris-HCl solution with a pH of 8.5-9.5;

[0024] S4. Calcination: The modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder obtained in step S3, 7.6-8 parts by weight of lithium carbonate, and 0.1-0.12 parts by weight of potassium oxide are mixed and ball-milled for 1-3 hours, calcined at 300-400°C for 1-5 hours, heated to 500-600°C, calcined for 1-5 hours, heated to 700-900°C, calcined for 2-15 hours, and cooled to room temperature to obtain a composite material for a positive electrode of a lithium-ion battery.

[0025] The present invention further protects a composite material for a positive electrode of a lithium ion battery obtained by the above preparation method.

[0026] The present invention further protects the use of the composite material for positive electrode of a lithium ion battery in preparing lithium ion batteries for household appliances, mobile phones, tablets and computers.

[0027] The present invention has the following beneficial effects:

[0028] Spinel LiMn2O4 has a three-dimensional tunnel structure that is conducive to the migration of lithium ions. The oxygen anions are arranged in a face-centered cubic close-packed manner at 32e (Wyckoff position), Mn (III) and Mn (IV) are located at the 16d octahedral interstitial position, and Li + Located at the 8a tetrahedral position in the three-dimensional skeleton channel. However, spinel LiMn2O4 will suffer severe capacity decay due to a series of physical or chemical reactions during charge and discharge, which will lead to structural destruction.

[0029] La doping can replace part of Mn 3+ The Jahn-Teller effect is suppressed, thereby improving the cycle performance of lithium manganese oxide; Ce doping has better cycle performance and rate performance. However, if a large amount of low-valent cations are doped, the electrochemically active Mn 3+ decrease, resulting in a decrease in the specific capacity of the material.

[0030] Ti doping enhances the stability of the material's crystal structure and reduces the side reactions between the particle surface and the electrolyte. Ti doping can increase Li + diffusion, while reducing the internal resistance of the electrode, doping Ti 4+ Can replace part of Mn 4+ To achieve the effect of inhibiting the dissolution of Mn, thereby improving the stability of the material. 4+ 、Ti 4+ High-valent cations replace Mn 4+ It not only does not affect the capacity of LiMn2O4, but also makes the crystal structure of LiMn2O4 more stable. At the same time, the doping of Ti and Si reduces the doping of other low-valent metal ions, and at the same time, it also has a good synergistic effect of improving performance.

[0031] The present invention adopts La / Ce doping to prepare titanium silicalite, and by adding Mn3O4, the conventional calcination time is too long and cannot achieve uniform dispersion at the atomic level. The present invention adopts the self-propagating combustion method to uniformly mix the raw materials at the atomic level and shorten the calcination time.

[0032] The present invention adopts polydopamine to coat modified La / Ce doped Si / Ti oxide coated Mn3O4 powder. On the one hand, it can promote the adsorption and uniform dispersion of the prepared modified La / Ce doped Si / Ti oxide coated Mn3O4 powder with lithium carbonate and potassium oxide. On the other hand, under high-temperature calcination, polydopamine will be carbonized to form a carbon layer and doped with N, so that the product is coated with a conductive carbon layer material, has a highly enhanced rate capability, can withstand high rates, and has a high capacity retention rate at high temperatures.

[0033] K doping can significantly improve the high-rate discharge specific capacity, improve the rate performance and high-temperature cycle stability. The reasons for the performance improvement are as follows: First, K ions expand the structural skeleton of spinel, expand the lithium extraction / embedding channels, and improve the lithium ion mobility; second, K ions can participate in the electronic conduction of the positive electrode, reduce the internal resistance of the battery, and improve the conductivity of the material; third, the synergistic effect of co-doping of K and N ions enhances the diffusion capacity of lithium ions.

[0034] The composite material for lithium ion battery positive electrode prepared by the invention improves the cycle performance of lithium manganate, reduces the internal resistance of the electrode, improves the high-rate discharge specific capacity, has better rate performance and high-temperature cycle stability, has a high capacity retention rate for multiple cycles, and has broad application prospects. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment provides a method for preparing a composite material for a lithium ion battery positive electrode, comprising the following steps:

[0038] S1. Preparation of La / Ce-doped silicon-titanium sol: 1 g of lanthanum chloride and 2 g of cerium chloride were dissolved in 100 mL of water to obtain solution A, 15 g of methyl orthosilicate and 8 g of tetrabutyl titanate were dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 7 g of 1 mol / L hydrochloric acid was added dropwise to form a sol, and La / Ce-doped silicon-titanium sol was obtained;

[0039] S2. Preparation of La / Ce doped Si / Ti oxide coated Mn3O4 powder: 10g Mn3O4 was added to 20g La / Ce doped silicon titanium sol, stirred and mixed for 30min, heated to 180°C, and a self-propagating combustion reaction was performed to obtain fluffy La / Ce doped Si / Ti oxide coated Mn3O4 powder;

[0040] S3. Polydopamine modification: The La / Ce-doped Si / Ti oxide-coated Mn3O4 powder prepared in step S2 was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.5 g of catalyst were added, heated to 40 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder;

[0041] The catalyst is a Tris-HCl solution with a pH of 8.5;

[0042] S4. Calcination: The modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder obtained in step S3, 2 g of lithium carbonate, and 0.01 g of potassium oxide were mixed and ball-milled for 1 h, calcined at 300°C for 2 h, heated to 500°C, calcined for 2 h, heated to 700°C, calcined for 5 h, and cooled to room temperature to obtain a composite material for a lithium-ion battery positive electrode.

[0043] Example 2

[0044] This embodiment provides a method for preparing a composite material for a lithium ion battery positive electrode, comprising the following steps:

[0045] S1. Preparation of La / Ce-doped silicon-titanium sol: 2 g of lanthanum chloride and 3 g of cerium chloride were dissolved in 100 mL of water to obtain solution A, 20 g of ethyl orthosilicate and 10 g of tetrabutyl titanate were dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 10 g of 2 mol / L hydrochloric acid was added dropwise to form a sol, and La / Ce-doped silicon-titanium sol was obtained;

[0046] S2. Preparation of La / Ce doped Si / Ti oxide coated Mn3O4 powder: 10g Mn3O4 was added to 30g La / Ce doped silicon titanium sol, stirred and mixed for 30min, heated to 200°C, and a self-propagating combustion reaction was performed to obtain fluffy La / Ce doped Si / Ti oxide coated Mn3O4 powder;

[0047] S3. Polydopamine modification: The La / Ce-doped Si / Ti oxide-coated Mn3O4 powder prepared in step S2 was added to 200 mL of water, 6 g of dopamine hydrochloride and 1 g of catalyst were added, heated to 50 ° C, stirred for 5 h, centrifuged, washed, and dried to obtain a modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder;

[0048] The catalyst is a Tris-HCl solution with a pH of 9.5;

[0049] S4. Calcination: The modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder obtained in step S3, 2.4 g of lithium carbonate, and 0.02 g of potassium oxide were mixed and ball-milled for 3 h, calcined at 400°C for 5 h, heated to 600°C, calcined for 5 h, heated to 900°C, calcined for 15 h, and cooled to room temperature to obtain a composite material for a positive electrode of a lithium-ion battery.

[0050] Example 3

[0051] This embodiment provides a method for preparing a composite material for a lithium ion battery positive electrode, comprising the following steps:

[0052] S1. Preparation of La / Ce-doped silicon-titanium sol: 1.5 g of lanthanum chloride and 2.5 g of cerium chloride were dissolved in 100 mL of water to obtain solution A, 17 g of tetraethyl orthosilicate and 9 g of tetrabutyl titanate were dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 8 g of 1.5 mol / L hydrochloric acid was added dropwise to form a sol, and La / Ce-doped silicon-titanium sol was obtained;

[0053] S2. Preparation of La / Ce doped Si / Ti oxide coated Mn3O4 powder: 10g Mn3O4 was added to 25g La / Ce doped silicon titanium sol, stirred and mixed for 30min, heated to 190°C, and a self-propagating combustion reaction was performed to obtain fluffy La / Ce doped Si / Ti oxide coated Mn3O4 powder;

[0054] S3. Polydopamine modification: The La / Ce-doped Si / Ti oxide-coated Mn3O4 powder prepared in step S2 was added to 200 mL of water, 5 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain a modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder;

[0055] The catalyst is a Tris-HCl solution with a pH of 9;

[0056] S4. Calcination: The modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder obtained in step S3, 2.2 g of lithium carbonate, and 0.015 g of potassium oxide were mixed and ball-milled for 2 h, calcined at 350°C for 3 h, heated to 550°C, calcined for 3 h, heated to 800°C, calcined for 10 h, and cooled to room temperature to obtain a composite material for a positive electrode of a lithium-ion battery.

[0057] Comparative Example 1

[0058] Compared with Example 3, the difference is that lanthanum chloride is not added in step S1.

[0059] The details are as follows:

[0060] S1. Preparation of Ce-doped silicon titanium sol: 4 g of cerium chloride was dissolved in 100 mL of water to obtain solution A, 17 g of tetraethyl orthosilicate and 9 g of tetrabutyl titanate were dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 8 g of 1.5 mol / L hydrochloric acid was added dropwise to form a sol, and Ce-doped silicon titanium sol was obtained.

[0061] Comparative Example 2

[0062] Compared with Example 3, the difference is that cerium chloride is not added in step S1.

[0063] The details are as follows:

[0064] S1. Preparation of La-doped silica-titanium sol: 4 g of lanthanum chloride was dissolved in 100 mL of water to obtain solution A, 17 g of ethyl orthosilicate and 9 g of tetrabutyl titanate were dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 8 g of 1.5 mol / L hydrochloric acid was added dropwise to form a sol, and La-doped silica-titanium sol was obtained.

[0065] Comparative Example 3

[0066] Compared with Example 3, the difference is that lanthanum chloride and cerium chloride are not added in step S1.

[0067] The details are as follows:

[0068] S1. Preparation of silica-titanium sol: 17 g of ethyl orthosilicate and 9 g of tetrabutyl titanate were dissolved in 150 mL of ethanol to obtain solution B. 100 mL of water and solution B were mixed and stirred for 15 min. 8 g of 1.5 mol / L hydrochloric acid was added dropwise to form a sol to obtain silica-titanium sol.

[0069] Comparative Example 4

[0070] Compared with Example 3, the difference is that tetraethyl orthosilicate is not added in step S1.

[0071] The details are as follows:

[0072] S1. Preparation of La / Ce-doped titanium sol: 1.5 g of lanthanum chloride and 2.5 g of cerium chloride were dissolved in 100 mL of water to obtain solution A, 26 g of tetrabutyl titanate was dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 8 g of 1.5 mol / L hydrochloric acid was added dropwise to form a sol, and La / Ce-doped titanium sol was obtained.

[0073] Comparative Example 5

[0074] Compared with Example 3, the difference is that tetrabutyl titanate is not added in step S1.

[0075] The details are as follows:

[0076] S1. Preparation of La / Ce-doped silica sol: 1.5 g of lanthanum chloride and 2.5 g of cerium chloride were dissolved in 100 mL of water to obtain solution A, 26 g of tetraethyl orthosilicate was dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 8 g of 1.5 mol / L hydrochloric acid was added dropwise to form a sol, and La / Ce-doped silica sol was obtained.

[0077] Comparative Example 6

[0078] Compared with Example 3, the difference is that step S3 is not performed.

[0079] The details are as follows:

[0080] S1. Preparation of La / Ce-doped silicon-titanium sol: 1.5 g of lanthanum chloride and 2.5 g of cerium chloride were dissolved in 100 mL of water to obtain solution A, 17 g of tetraethyl orthosilicate and 9 g of tetrabutyl titanate were dissolved in 150 mL of ethanol to obtain solution B, solution A and solution B were mixed and stirred for 15 min, 8 g of 1.5 mol / L hydrochloric acid was added dropwise to form a sol, and La / Ce-doped silicon-titanium sol was obtained;

[0081] S2. Preparation of La / Ce doped Si / Ti oxide coated Mn3O4 powder: 10g Mn3O4 was added to 25g La / Ce doped silicon titanium sol, stirred and mixed for 30min, heated to 190°C, and a self-propagating combustion reaction was performed to obtain fluffy La / Ce doped Si / Ti oxide coated Mn3O4 powder;

[0082] S3. Calcination: The La / Ce-doped Si / Ti oxide-coated Mn3O4 powder obtained in step S2, 2.2 g of lithium carbonate, and 0.015 g of potassium oxide were mixed and ball-milled for 2 h, calcined at 350°C for 3 h, heated to 550°C, calcined for 3 h, heated to 800°C, calcined for 10 h, and cooled to room temperature to obtain a composite material for a lithium-ion battery positive electrode.

[0083] Comparative Example 7

[0084] Compared with Example 3, the difference is that potassium oxide is not added in step S4.

[0085] The details are as follows:

[0086] S4. Calcination: The modified La / Ce-doped Si / Ti oxide-coated Mn3O4 powder obtained in step S3 and 2.215 g of lithium carbonate were mixed and ball-milled for 2 h, calcined at 350°C for 3 h, heated to 550°C, calcined for 3 h, heated to 800°C, calcined for 10 h, and cooled to room temperature to obtain a composite material for a lithium-ion battery positive electrode.

[0087] Test Example 1

[0088] The composite material for positive electrode of lithium ion battery prepared in Example 1-3 or Comparative Example 1-7, conductive agent (SP), polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 9:1:1, N-methylpyrrolidone (NMP) was used as an organic solvent, placed in a mortar, fully ground and evenly coated on aluminum foil, dried at 60°C, and die-cut into circular electrode sheets with a diameter of 13 mm for later use. CR2025 button batteries (pressure of about 5MPa) were assembled in a glove box filled with argon in the order of negative electrode sheet (lithium foil), diaphragm, electrolyte, and positive electrode sheet. The diaphragm was a polypropylene film, and the electrolyte was a solution of 1 mol / L LiPF6, ethylene carbonate: dimethyl carbonate (volume ratio 1:1).

[0089] The electrical performance test and evaluation were carried out, and the results are shown in Table 1.

[0090] Table 1

[0091]

[0092] It can be seen from the above table that the composite materials for lithium ion battery positive electrode prepared in Examples 1-3 of the present invention have better electrochemical properties.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material for a lithium ion battery positive electrode, characterized in that: La and Ce doped silicon-titanium sol was prepared, Mn3O4 was added, and the mixture was heated for self-propagating combustion reaction to obtain fluffy La and Ce doped Si / Ti oxide coated Mn3O4 powder. The surface was modified by coating with polydopamine, mixed with lithium carbonate and potassium oxide and ball milled. After three-stage calcination and cooling to room temperature, spinel lithium manganese oxide, a composite material for positive electrode of lithium-ion batteries, was obtained.

2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. Preparation of La and Ce doped silicon titanium sol: lanthanum chloride and cerium chloride were dissolved in water to obtain solution A, alkyl orthosilicate and tetrabutyl titanate were dissolved in ethanol to obtain solution B, solution A and solution B were mixed uniformly, hydrochloric acid was added dropwise to form a sol, and La and Ce doped silicon titanium sol was obtained; S2. Preparation of La and Ce doped Si / Ti oxide coated Mn3O4 powder: Mn3O4 was added to La and Ce doped silicon titanium sol, stirred and mixed evenly, and heated for self-propagating combustion reaction to obtain fluffy La and Ce doped Si / Ti oxide coated Mn3O4 powder; S3. Polydopamine modification: La and Ce doped Si / Ti oxide coated Mn3O4 powder was added to water, dopamine hydrochloride and a catalyst were added, heated and stirred for reaction, centrifuged, washed, and dried to obtain modified La and Ce doped Si / Ti oxide coated Mn3O4 powder; S4. Calcination: The modified La and Ce doped Si / Ti oxide coated Mn3O4 powder, lithium carbonate and potassium oxide are mixed and ball-milled, calcined at a first temperature for a first time period, heated to a second temperature, calcined for a second time period, heated to a third temperature, calcined for a third time period, and cooled to room temperature to obtain a composite material for a positive electrode of a lithium-ion battery.

3. The preparation method according to claim 2, characterized in that: The mass ratio of lanthanum chloride, cerium chloride, alkyl orthosilicate, tetrabutyl titanate and hydrochloric acid in step S1 is (1-2): (2-3): (15-20): (8-10): (7-10), and the concentration of hydrochloric acid is 1-2 mol / L.

4. The preparation method according to claim 2, characterized in that: The heating in step S2 is to a temperature of 180-200°C.

5. The preparation method according to claim 2, characterized in that: The mass ratio of the Mn3O4, La and Ce doped silica-titanium sol, dopamine hydrochloride, catalyst, lithium carbonate and potassium oxide is 10: (20-30): (4-6): (0.5-1): (2-2.4): (0.01-0.02).

6. The preparation method according to claim 2, characterized in that: The temperature of the heating and stirring reaction in step S3 is 40-50° C., the time is 3-5 hours, and the catalyst is a Tris-HCl solution with a pH of 8.5-9.

5.

7. The preparation method according to claim 2, characterized in that: The ball milling time in step S4 is 1-3 hours, the first temperature is 300-400°C, the time is 1-5 hours, the second temperature is 500-600°C, the time is 1-5 hours, and the third temperature is 700-900°C, the time is 2-15 hours.

8. The preparation method according to claim 2, characterized in that: The specific steps include: S1. Preparation of La and Ce doped silicon titanium sol: 1-2 parts by weight of lanthanum chloride and 2-3 parts by weight of cerium chloride are dissolved in water to obtain solution A, 15-20 parts by weight of alkyl orthosilicate and 8-10 parts by weight of tetrabutyl titanate are dissolved in ethanol to obtain solution B, solution A and solution B are mixed uniformly, 7-10 parts by weight of 1-2 mol / L hydrochloric acid is added dropwise to form a sol, and La and Ce doped silicon titanium sol is obtained; S2. Preparation of La and Ce doped Si / Ti oxide coated Mn3O4 powder: 14-15 parts by weight of Mn3O4 is added to 20-30 parts by weight of La and Ce doped silicon titanium sol, stirred and mixed for 30 minutes, heated to 180-200°C, and subjected to self-propagating combustion reaction to obtain fluffy La and Ce doped Si / Ti oxide coated Mn3O4 powder; S3. Polydopamine modification: The La and Ce doped Si / Ti oxide coated Mn3O4 powder prepared in step S2 is added to water, 4-6 parts by weight of dopamine hydrochloride and 0.5-1 parts by weight of catalyst are added, heated to 40-50 ° C, stirred for 3-5h, centrifuged, washed, and dried to obtain modified La and Ce doped Si / Ti oxide coated Mn3O4 powder; The catalyst is a Tris-HCl solution with a pH of 8.5-9.5; S4. Calcination: The modified La and Ce doped Si / Ti oxide coated Mn3O4 powder obtained in step S3, 7.6-8 parts by weight of lithium carbonate, and 0.1-0.12 parts by weight of potassium oxide are mixed and ball-milled for 1-3 hours, calcined at 300-400°C for 1-5 hours, heated to 500-600°C, calcined for 1-5 hours, heated to 700-900°C, calcined for 2-15 hours, and cooled to room temperature to obtain a composite material for a positive electrode of a lithium-ion battery.

9. A composite material for positive electrode of a lithium ion battery obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the composite material for lithium ion battery positive electrode as claimed in claim 9 in preparing lithium ion batteries for household appliances, mobile phones, tablets and computers.

Citation Information

Patent Citations

  • Porous C / Li2MSiO4 / C (M=Fe, Mn, Co) composite positive electrode material and preparation method thereof

    CN102315438A

  • Lithium ion battery cathode material with function of rapid charging and preparation method thereof

    CN102347472A